# 20x^3+13x^2+2x=

## Simple and best practice solution for 20x^3+13x^2+2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 20x^3+13x^2+2x= equation:

Simplifying 20x^{3}+ 13x^{2}+ 2x = 0 Reorder the terms: 2x + 13x^{2}+ 20x^{3}= 0 Solving 2x + 13x^{2}+ 20x^{3}= 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(2 + 13x + 20x^{2}) = 0 Factor a trinomial. x((2 + 5x)(1 + 4x)) = 0## Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0## Subproblem 2

Set the factor '(2 + 5x)' equal to zero and attempt to solve: Simplifying 2 + 5x = 0 Solving 2 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = 0 + -2 5x = 0 + -2 Combine like terms: 0 + -2 = -2 5x = -2 Divide each side by '5'. x = -0.4 Simplifying x = -0.4## Subproblem 3

Set the factor '(1 + 4x)' equal to zero and attempt to solve: Simplifying 1 + 4x = 0 Solving 1 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 4x = 0 + -1 4x = 0 + -1 Combine like terms: 0 + -1 = -1 4x = -1 Divide each side by '4'. x = -0.25 Simplifying x = -0.25## Solution

x = {0, -0.4, -0.25}

### See similar equations:

| 5y=2x-4 | | n^2-13n+36=0 | | -45y-58=y-49 | | 6x^2+13x+5= | | (x^2-2x+4)+(2x+1)-(x^2+5)= | | (4q-5r+7p)-(7r-2q+3p)= | | x-79=60 | | -10=10(k+-9) | | 0.60(z-300)+0.05x=0.70z-205 | | 2x-6=5x-18 | | 17x-4=0 | | 4t+7-t=9 | | y/4=-7 | | 2(3n-8)4n=10 | | 4(x-8)=2x | | 3x^4-6x^2-2=0 | | 12(n+5)-10=11n+2 | | -(-3+10)= | | 17y=0 | | x+(x+1)=66 | | 39-12w=7-16 | | 4x^2-121= | | 53-x=2x+3 | | (x^2-2x+1)+(y^2-4y+4)=9 | | 8u+3u=35 | | -7+[-(-9)]= | | 12x^3+4x^2+40x=0 | | 5x-23y=23 | | 0=-16x^2+64+720 | | x+0.25x=9 | | -2+3x=2x+6+x | | (4x-2)-(-3x-5)=3 | | 2t^2+9t-26=0 | | 5x-23y=7 | | r^4+9y+15=0 | | 12x+16=4x+8 | | 10-2(2x+1)=4(x-2) | | -2x^2=20 | | 0=3x^2+122x+3721 | | 3h^2+4h-14=0 | | 3h^2+4h-224=0 | | 9=5-4x | | -x^2+5x+12=0 | | 3x^2+20=-32 | | 5x+21=x^2+3 | | 3x^2+20x=-32 | | 5x+21=(x^2)+9 | | -3x+7=-x-1 | | 15x-3=30x-3 | | 15x-3=30x-2 | | 1-2p+5=4p+6 | | 2y^2+7y=-5 | | 13x+14=2x-5 | | 5x(x)=90 | | x/4-1=-x/2+8 | | 180-x=3(90-x)-38 | | 4r^2-4r+1=0 | | 13x^2+10x+1=0 | | 5n-n=9 | | 5n-n=9+3 | | a(3tx-2b)=x(dx-2) | | 3(x+1)=2x-(4-x) | | 3x+2(x+3)=30 | | 4x-5=36x-2 | | 72+-14=36 |